Taxonomic study on the spider wasp genus Ceropales Latreille, 1796 (Pompilidae: Ceropalinae) with description of two new species from India - Anju, K.; Thejass, P.; Binoy, C.; Kumar, P. Girish (Zootaxa, 2023)
The spider wasp genus Ceropales Latreille, 1796 from India was studied, resulting in the discovery of two new species in the nominotypical subgenus: Ceropales (Ceropales) anaghae Anju, Girish Kumar & Thejass, sp. nov. and C. (C.) keralaensis Anju, Binoy & Thejass, sp. nov. Description of the new species with illustrations, comparisons with congeners and a key to Indian species of the subgenus are also provided.